Development of Authentic Assessment Instruments of the Attitudes Domain for Grade IV Students in Elementary School - Ramadan, Zaka Hadikusuma; Hastuti, Tity (International Journal of Elementary Education, 2021)
This research is based on teachers who have difficulty how to compile instruments and carry out authentic assessments, especially in the realm of attitudes. The research objective was to develop an authentic assessment instrument in the realm of attitudes for fourth grade elementary school students. The method used was formative research which was carried out in two stages, namely the preliminary stage and the formative evaluation stage. The research instrument used expert evaluation sheet validation, material and thematic. Data analysis using descriptive analysis. Authentic assessment instruments in the realm of attitudes for fourth grade students developed on the theme "My Heroes" in the form of an assessment rubric and an assessment format. The results of expert validation obtained an average percentage of 97.50% in the very good category. The results of the trial showed that the assessment instruments were used by 2 teachers in assessing the same students, the results were that the teachers had similarities in their assessments. So that the assessment instrument is said to be valid.